IR microspectroscopic imaging discriminates isogenic null waxy from parent wheats with lipid class profile supported by compositional analyses - Brewer, Lauren Renee (Kansas State University, 2009)
Isogenic waxy wheat lines differ from their non waxy (normal) parents in functionality, end use, and chemical (i.e. amylopectin/amylose, lipid) contents. Other investigations of waxy and parent wheats involved the carbohydrate and protein fractions. The goal of this work is to apply chemical images to discriminate between the waxy and parent wheats and define the contribution of contrasting lipid profiles. Recent waxy topics include current interest in plant breeding activity to develop new lines that incorporate desirable traits with advantageous success in baking and milling, and the differences needed in milling techniques for waxy versus normal wheats that may be associated with lipids. From our empirical preliminary success in sorting parent wheat kernels from waxy wheat full null specimens by nearIR chemical imaging it was anticipated that using fundamental vibrational spectra in the mid infrared would provide the chemical basis of discrimination. FT-IR microspectroscopic in situ probing and imaging of kernel frozen sections was applied to genetically pure, well documented isogenic breeding lines. With the use of high spatial resolution, elucidation of fundamental vibrations of mid IR provides chemical manifestation of the genetic expression that differentiates waxy wheats from their parent wheats. Comparison between numerous contiguous pixels, typically 3,000 for each type, establishes a consensus and a mean spectrum with characteristic bands for waxy and parent. Extractions with solvents of differing polarity were employed to aid in lipid extraction in situ and kernel extracted endosperm. Differences between kernel sections of waxy and parent are observed using FT-IR microspectroscopic imaging. However, revealing lipid class contribution to the molecular bands required infrared analysis after selective extraction. Triple mass spectrometry of lipid molecule ions was used for compositional analyses to enhance lipid class profile distinction. A normal and waxy advanced breeding line wheat were also analyzed via the same methods. It was noted that digalactoslydyglyercides are the most abundant lipids in all samples, however the relative lipid profiles of normal wheat versus waxy wheat differ as well as tetraploid versus hexaploid. It is observed that in the endosperm of all parent wheat versus waxy wheat specimens analyzed, all waxy wheat specimens contained higher lipid content. Methods were also applied to partial waxy isogenic cultivars to determine detection limits that correspond to the degree of waxy genetic expression.
Keywords: waxy wheat; microspectroscopy; imaging; genetics; mass spectrometry; lipids; Agriculture, Food Science and Technology (0359); Chemistry, Analytical (0486)